2008
DOI: 10.1007/s00726-008-0137-3
|View full text |Cite
|
Sign up to set email alerts
|

Highlights at the gate of tryptophan catabolism: a review on the mechanisms of activation and regulation of indoleamine 2,3-dioxygenase (IDO), a novel target in cancer disease

Abstract: Indoleamine 2,3-dioxygenase (IDO) catalyzes the first and rate-limiting step of Kynurenine pathway along the major route of Tryptophan catabolism. The scientific interest in the enzyme has been growing since the observations of the involvement of IDO in the mechanisms of immune tolerance and in the mechanisms of tumor immuno-editing process. In view of this latter observation, in particular, preclinical studies of small molecule inhibitors of the enzyme have indicated the feasibility to thwart the immuno-editi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 56 publications
1
78
0
Order By: Relevance
“…Indeed, reduction of this group (18) or its removal altogether (19) led to inactive compounds thus confirming the requirement for an iron coordinating group (Table 4). Oxime 20 is endowed with an in vivo inhibitory potency similar to that of ketone 7a but surprisingly, this compound is not active in vitro.…”
Section: Ido Inhibition Through Interaction With the Heme Iron Bindinsupporting
confidence: 52%
See 1 more Smart Citation
“…Indeed, reduction of this group (18) or its removal altogether (19) led to inactive compounds thus confirming the requirement for an iron coordinating group (Table 4). Oxime 20 is endowed with an in vivo inhibitory potency similar to that of ketone 7a but surprisingly, this compound is not active in vitro.…”
Section: Ido Inhibition Through Interaction With the Heme Iron Bindinsupporting
confidence: 52%
“…Indeed, results from in vitro and in vivo studies have suggested an improvement of the efficacy of therapeutic vaccination or chemotherapy by concomitant administration of an IDO inhibitor thus highlighting IDO as an attractive target. 12,13,[15][16][17] Until recently, the best known IDO inhibitors 18 displayed affinities in the micromolar range and comprised mainly Trp derivatives such as 1-methyltryptophan (1MT) 19 (K i = 37 lM) or b-carbolines (K i $0.12 mM). 20 Other indole-based IDO inhibitors, such as brassinin 21,22 and methylthiohydantoin-tryptophan (MTH-Trp) 13 have been described.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, the best known IDO inhibitors [15] displayed affinities in the micromolar range and comprised mainly Trp derivatives such as 1-methyl-L-tryptophan (1MT) [16] (K i w 34 mM) and b-carbolines [17]. In 2006, potent nanomolar inhibitors were isolated from marine invertebrate extracts [18,19] At the same time, new brassinin-based IDO inhibitors were published [20,21], the best having a K i of 12 mM.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis, together with its expression in such a large number of human diseases has firmly established IDO-1 as an appealing drug target. [12][13][14][15][16][17][18] Furthermore, Zheng and co-workers have shown that murine melanoma cells, stably transformed with an IDO-1-silencing construct, exhibited a reduced capacity to form tumours compared with the unmodified parental melanoma cells when inoculated into recipient mice. [19] Moreover, tumours developing from the wild-type parental cells regressed when injected intra-tumourally with an anti-IDO siRNA.…”
Section: Introductionmentioning
confidence: 99%